Variable Climates Lead to Varying Phenotypes: “Weird” Mammalian Torpor and Lessons From Non-Holarctic Species - Nowack, Julia; Levesque, Danielle L.; Reher, Stephanie; Dausmann, Kathrin H. (Frontiers in Ecology and Evolution, 2020)
Mammalian heterotherms, species that employ short or long periods of torpor, are found in many different climatic regions. Although the underlying physiological mechanisms of heterothermy in species from lower latitudes (i.e. the tropics and southern hemisphere) appear analogous to those of temperate and arctic heterotherms, the ultimate triggers and resulting patterns of energy expenditure and body temperature are often noticeably different. Phenotypic flexibility in the patterns of thermoregulation in non-Holarctic species can be extensive (depending on body condition, environmental parameters and species competition) and the factors responsible for inducing heterothermy are more variable in non-Holarctic species. As well as being a regular adaptation to seasonality, heterothermy can also be employed as a response to unpredictability in environmental parameters and as a response to emergency situations. Non-Holarctic heterotherms also challenge the notion that regular inter-bout arousals during hibernation are obligatory and suggest all that is necessary to maintain proper functioning during hibernation is an occasional passive return to -or maintenance of - a relatively high body temperature. The study of non-Holarctic heterotherms has led to the conclusion that heterothermy must be defined on the basis of mechanistic, physiological parameters, and not solely by body temperature; yet we are still limited in our abilities to record such mechanistic parameters in the field. It is now believed that homeothermy in mammals evolved in hot climates via an ancestral heterothermic state. Similar to extant warm-climate heterotherms, early mammals could have relied mainly on passive body temperature regulation with a capacity for short- to longer-term up-regulation of metabolism when needed. Hibernation, as seen in temperate and arctic species may then be a derived state of this ancestral heterothermy, and the study of torpor in warm climates can provide potential models for the energetics of early mammals.